(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Despite the recognized stability of the rabies virus (RABV), antigenic and genetic differences among strains isolated from different species have been found. Different factors may be involved in generating heterogeneity in RABV, including duration of infection, virus load and host immune response. This work was carried out in order to examine the antigenic and genetic stability of RABVs isolated from different natural reservoirs and to help the understanding of viral pathogeny after consecutive passages in different systems. In this study were used tree RABV strains, one isolated from canine, one isolated from haematophagous bat and the standard rabies virus strain (Challenge Virus Standard – CVS). These strains were submitted to five consecutive passages in mice and in cells. The consecutive passages in mice were made by intracerebral route, for that, groups of six mice were submitted to five inoculations with each one of the three RABV strains. The inoculated mice were observed daily and the dates of death were recorded. The consecutive passages in cells were made in “Neuroblast albino mouse” (N2a) cell lineage, for that, the strains were inoculated in suspension cells and incubated for 72 hours, subsequently, cells were frozen and thawed three times. Both mice and cell passages were submitted to antigenic and genetic characterization. The antigenic characterization was determined by indirect immunofluorescence (IIF) with a panel of eight monoclonal antibodies (Mabs) raised to RABV antigens. For the genetic characterization the total RNA was extracted with Trizol and submitted to reverse transcription-polymerase chain reaction (RT-PCR) with primers targeting the N and the G genes, the amplicons obtained were subjected to nucleotide sequence analysis. The RABV sequences were analyzed using Bioedit package.